Prevalence of Benign Vocal Fold Lesions in Ear, Nose, and Throat Outpatient Unit of Dr. Soetomo General Hospital, Surabaya, Indonesia - Lucia Miranti Hardianingwati; Diar Mia Ardani (Biomolecular and Health Science Journal, 2020)
Introduction: Benign vocal fold lesions reduce the efficiency of sound production. Reports of dysphonia cases caused by vocal principles in Indonesia are still very limited. This study aimed to determine incidence and prevalence of benign vocal fold lesions, namely vocal cord nodules, cysts, and polyps.Methods: A descriptive retrospective study was conducted using patient’s medical record of Ear, Nose, and Throat (ENT) Outpatient Unit. Dysphonia patients with benign vocal cord abnormalities were identified. The data analyzed using descriptive analytic.Results: There were 20 patients with benign vocal fold lesions, consisting of 13 patients (65%) with nodules, 3 patients (15%) with polyps, and 4 patients (20%) with cysts. The ratio of male and female patients was 1: 1. Most patients belonged to age group of 20-59 years (12 patients; 60%). In term of occupation, most patients belonged to group III, which is a group of workers who are not professional voice users (12 patients; 60%). Most vocal fold lesions were found in the 1/3 of bilateral anterior (17 patients; 85%). Most therapy was non-operative in 13 patients (65%). Conclusion: Benign vocal fold lesions, including vocal cord nodules, polyps, and cysts, are found in all patients with dysphonic complaints. The prevalence of dysphonia symptoms is quite high every year, but only a small portion are diagnosed with benign vocal cord lesion.